Proliferasi Nano Kitosan dan Platelet Rich Plasma dari Sel Pre-Osteoblast dengan Ki67 sebagai Pengganti Marker In Vitro - Wedagama, Dewa Made (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
This study investigated the effect of nano-chitosan mix with platelet rich plasma (PRP) to proliferation rate of pre-osteoblast cell with incubation time used in vitro culture system. The culture media of pre-osteoblast cell MC3T3-E1 used alpha-MEM, 2mm L-glutamine, 1mm sodium pyruvate, 10% FBS and 10% pen strep in 25cm2 flask bottle and incubated in an incubator with 5% CO2 at a temperature of 37oC until the cell was confluent 70-80% and planting in well-24 to give treatments. Treatment was divided into two groups, nano-chitosan+PRP and hydroxyapatite+PRP. The proliferation of pre-osteoblast cells saw with immunocytochemical staining and proliferation of cells were counted and investigated with confocal laser scanning microscope (CLSM). The normality of sample data was analyzed with Shapiro-Wilk. Comparison test used independent sample t-test and one-way ANOVA (F-test). All data were analyzed with SPSS software. The experiment results showed that nano-chitosan+PRP can accelerate proliferation than hydroxyapatite+PRP of 0% and 10% concentrations. The independent sample t-test showed there were a significant difference (p=0.010<) from proliferation rate mean (0%) between treatment group nano-chitosan+PRP (1076.3±176.4au) and treatment group hydroxyapatite+PRP (659.5±272.7au) on five days incubation time, and proliferation mean (10%) between treatment group of nano-chitosan+PRP (710.3±109.7au) and hydroxyapatite+PRP (581.8±76.4au) on seven days incubation time. Based on proliferation mean (0%) and (10%), the treatment group of nano-chitosan+PRP with five- and seven-days incubation have higher mean than 0% and 10% on treatment group nano-chitosan and PRP and can accelerate bone healing with incubation time of five and seven days compared to treatment group of hydroxyapatite+PRP.